Free‐Radical Carbo‐Alkenylation of Olefins: Scope, Limitations and Mechanistic Insights. Issue 10 (23rd January 2017) - Beniazza, Redouane; Liautard, Virginie; Poittevin, Clément; Ovadia, Benjamin; Mohammed, Shireen; Robert, Frédéric; Landais, Yannick
Abstract: The three‐component free‐radical carbo‐alkenylation of electron‐rich olefins has been studied, varying the substitution pattern in the alkene, in the radical precursor and in the final acceptor. New vinylsulfones were also prepared and their reactivity investigated. The scope and limitations of the process was established, and the reaction mechanism clarified using selected dienes as radical clocks. It was thus recognised that the reversible addition onto the olefin of the released sulfonyl group is an important event, which should not be overlooked when using such multicomponent carbo‐alkenylation reactions. Abstract : Radical and fast : Free‐radical carbo‐alkenylation of electron‐rich olefins has been studied, varying the substitution pattern on the alkene, the radical precursor and on the final sulfonyl acceptor. The scope and limitations of the process was established, and the reaction mechanism has been specified using selected dienes as radical clocks. It was shown that the reversible addition of the released sulfonyl group onto the olefin is important and should not be overlooked when using such processes.